Spatial Analysis of Determinants of Dengue Hemorrhagic Fever Cases in the Working Area of UPT BLUD Kaliorang East Kutai Health Center - Erwina, Brigita Win; Pakki, Irfansyah Baharuddin; Anggraeni, Ike (Civiliza Publishing, 2024)
Dengue hemorrhagic fever is one of the endemic diseases that continues to increase in various tropical regions, including Kaliorang East Kutai. This study is an observational analytical study with a control case approach, which was carried out from December 2023 to March 2024 in the work area of the UPT BLUD Kaliorang Health Center, East Kutai. The data used is secondary data from the 2021-2022 health report and the results of field observations. Data collection methods include environmental surveys, interviews, and spatial analysis using QGIS and GeoDa software. The results showed that there was a significant relationship between breeding place (OR = 8,636), resting place (OR = 4,000), and population density (OR = 5,921) with the incidence of dengue. In contrast, the 4M action did not show a significant relationship (OR = 1,000). The conclusion of this study emphasizes the importance of environmental management and increasing public awareness in the prevention of dengue fever in densely populated areas.